Outcomes of Living Donor Liver Transplantation in Patients With a History of Ruptured Hepatocellular Carcinoma - Lee, Hwi Yeol; Hong, Suk Kyun; Hong, Su young; Suh, Sanggyun; Han, Eui Soo; Lee, Jeong-Moo; Choi, YoungRok; Yi, Nam-Joon; Lee, Kwang-Woong; Suh, Kyung-Suk (Frontiers in Surgery, 2021)
Background: Liver transplantation (LT) is considered a contraindication in patients with a history of hepatocellular carcinoma (HCC) rupture because ruptured HCCs are classified as T4 in the current American Joint Committee on Cancer TNM system. This study aimed to assess living donor liver transplantation (LDLT) in these patients and elucidate the factors that may have affected their outcomes. Methods: Data of patients with a history of ruptured HCC who underwent LDLT between January 1999 and December 2019 were retrospectively reviewed. Results: Among 789 patients who underwent LDLT for HCC, five (0.64%) had a history of HCC rupture. Three patients (60%) were treated with transarterial chemoembolization (TACE) or transarterial embolization (TAE) for hemostasis, and two patients (40%) achieved spontaneous hemostasis. One of two patients who achieved spontaneous hemostasis underwent surgical resection and LT at one week and six years after the rupture, respectively. The other patient underwent LT two days after the rupture. Four patients (80%) survived for >5 years, while two patients (40%) experienced recurrence and succumbed during the median follow-up duration of 85.3 months (range, 12.4–182.7). The recurrence first developed at 4.3 and 17.0 months after LT; these patients were managed well using surgical resection for peritoneal seeding and TACE for intrahepatic HCC. Conclusion: LDLT can be considered a treatment method even in patients with a history of HCC rupture after full evaluation of tumor biology and risk of recurrence.